Comprehensive evaluation of high temperature tolerance of six rice varieties during grain-filling period based on key starch physicochemical indexes. (August 2021) - Yao, Dongping; Wu, Jun; Luo, Qiuhong; Shen, Hong; Zhuang, Wen; Xiao, Gui; Li, Jianwu; Li, Yingge; Deng, Qiyun; Lei, Dongyang; Bai, Bin
Abstract: In order to compare the high temperature tolerance of six rice varieties, field experiments using interval sowing population were conducted to select sowing batches at high temperature and normal temperature during grain filling period. High filling temperature decreased significantly head milled rice rate, setback, amylose content and the proportion of the short chain of amylopectin, and increased obviously chalkiness, breakdown, gelatinization temperature, gelatinization enthalpy, and the proportion of the medium chain of amylopectin. Analysis of variance indicated significant differences with respect to physicochemical indexes of the starches from six rice varieties under high temperature during grain filling stage. In addition, five starch physicochemical indexes including apparent amylose content, setback, breakdown, chalkiness and gelatinization enthalpy showed more sensitivity to high temperature. These indexes could be considered as key indexes to evaluate the high temperature tolerance of these six rice varieties. The experimental results showed that the high temperature tolerance of the six varieties – Huanghuazhan, Y liangyou 957, Taiyou 390, Tianyouhuazhan, Zhongzao 39, Y liangyou NO 1 – ranged from strong to weak. The regression equation showed similar results and indicated that the high temperature tolerance of different varieties could be preliminarily evaluated using the key physicochemical indexes of starch. Highlights: High temperature affected the starch structure to change physicochemical properties of rice. Five starch physicochemical indexes were selected to evaluate high temperature tolerance of rice. Setback, breakdown and chalkiness of rice starch were most sensitive to high filling temperature. The high temperature tolerance of six rice varieties was evaluated by key starch indexes.